A reduction type method for solving semi-infinite programming problems - Pereira, Ana I. (2006)
We present a reduction method for solving semi-infinite programming problems based on simulated annealing method equipped with a function stretching as a multi-local procedure and the penalty technique to solve the sequence of finite problems. To guarantee the global convergence of the algorithm we use an extension of penalty merit function. Our preliminary numerical results seem to show that the algorithm has a satisfactory computational behaviour.